Media and Armed Conflict: Protection of Journalists and Media Facilities under Human Rights Law and International Humanitarian Law - Seppelt, Rosalie (Department of Public Law, 2020)
This master thesis gives a comprehensive overview of the protection of journalists and media facilities in times of armed conflict. First, the thesis analyses, which legal regimes are applicable: international humanitarian or human rights law. In conclusion, it suggests a parallel application of both regimes while international humanitarian law is to be regarded as lex specialis in the event of an armed conflict. In the case of a discrepancy between norms of the two regulatory complexes, the lex specialis maxim solves the inconsistency as an interpretation rule. Thus, the human rights provision is interpreted in the light of the more specific humanitarian law provision. Secondly, the thesis examines the concrete norms under both legal regimes that protect journalists and media facilities. It finds that only human rights norms protect the work of journalists while international humanitarian law protects journalists as civilians and media facilities as civilian objects. In the event, that a (fatal) military attack on journalists or media facilities is justifiable under international humanitarian law, there exists a controversy with the right to life guaranteed in human rights law which is solved by means of the lex specialis principle. Finally, the extent of the de facto protection of journalists and media facilities in comparison to the assured de jure protection is tested. For this purpose, the effective protection of journalists and media facilities in general during the current South Sudan crisis is analysed as well as the protection of female journalists against gender-based rights violations in times of armed conflict. A huge discrepancy between the de jure granted protection and the actual protection is found in both cases. Therefore, this thesis stresses the need to adopt new binding international regulations specifically tailored to afford all journalists and media facilities the highest protection possible – especially in times of conflict.